Plasma Apolipoproteins Predicting the Occurrence and Severity of Diabetic Retinopathy in Patients With Type 2 Diabetes Mellitus - Zhang, Xinyuan; Nie, Yao; Gong, Zhizhong; Zhu, Meidong; Qiu, Bingjie; Wang, Qiyun (Frontiers in Endocrinology, 2022)
Objective: Apolipoproteins are amphipathic molecules and the major components of plasma lipoproteins. This study aims to investigate the effects of dysregulated apolipoprotein (apo) profiles and their ratios on type 2 diabetes mellitus (T2DM) and diabetic retinopathy (DR), further to test the hypothesis that altered serum level of apolipoproteins are strong biomarkers for DR. Research Design and Methods: This case-control study consists of 157 patients with T2DM including DM without DR, non-proliferative DR (NPDR), and proliferative DR (PDR). 58 age-, sex- matched healthy subjects were enrolled as normal controls. Blood biochemistry profile including serum levels of glucose, glycated hemoglobin (HbA1c), lipid profile [total cholesterol (TC), Triglycerides (TG), high and low-density lipoprotein (HDL-C, LDL-C)] were estimated. Apolipoproteins (apos, A-I, A-II, B, C-II, C-III, E) was evaluated by protein chips (Luminex technology). Apolipoprotein ratios and arteriosclerosis-associated plasma indices were calculated. The Kruskal–Wallis test, independent sample t-test or Mann–Whitney U test and multivariate regression analysis were performed to investigate the association of serum lipid biomarkers and the DR severity. Results: Serum level of apoA-I was negatively correlated with TC-(HDL-C)/ HDL-C (p <0.001), fasting glucose (p <0.001), HbA1c (p <0.001 ) and (p<0.001), while apoE, apoC-II/apoC-III, apoA-II/apoA-I was positively correlated with above traditional biomarkers (p <0.001). Single variable logistic analysis results showed that body mass index (BMI) (p= 0.023), DM duration (p <0.001), apoE (p <0.001), apoC-II/apo C-III (p <0.001), apoE/apoC-II (p <0.001), atherogenic index (p =0.013), fasting glucose (p <0.001), HbA1c (p <0.001), LPA (p =0.001), LDL-C/HDL-C (p =0.031) were risk factors for the occurrence and severity of DR. Multivariate logistic regression mode showed that apoC-II/apoC-III and apoB/non-HDL-C (p <0.001), apoE/apoC-II (p =0.001) were the independent risk factors for the occurrence and severity of DR, apopA-I and apoA-II are protective factors for DR, after controlling for the DM duration, HbA1c, fasting glucose and LPA. Conclusions: apoE, apoC-II/apoC-III, apoE/apoC-II, apoB/non-HDL-C could be used as novel biomarkers for occurrence and severity of DR, while apoA-I and apoA-II resulted as protective factors for DR.